PROMOSI SEBAGAI SALAH SATU UPAYA DALAM PEMASARAN PARIWISATA - Widoyono, Widoyono (Benefit, 2006)
Tourism is one of the sources of regional government revenue. It needs to be managingprofessionally. Promotion is one of the elements of marketing mix that play a significant role inattracting domestic and international tourist. Promotion in tourism needs a marketing institution, itcould be government or private institution (tourism bureau/BPW) Tourism bureau with governmentinstitution have to build tourism image in the society. Also, they have to be able to control the marketand understand what customer needs and wants.